2004
DOI: 10.1161/01.cir.0000124227.00670.ab
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Receptors 1 and 2 Differentially Regulate Survival, Cardiac Dysfunction, and Remodeling in Transgenic Mice With Tumor Necrosis Factor-α–Induced Cardiomyopathy

Abstract: Background-Tumor necrosis factor (TNF)-␣ plays a pathophysiological role in heart failure. Although both TNF receptor 1 (TNFR1) and 2 (TNFR2) are present in the heart, comparatively little is known about the role of TNFR2. Methods and Results-We bred TNFR1-knockout (KO) or TNFR2KO mice to transgenic (TG) mice with cardiac-specific overexpression of TNF-␣ and analyzed resultant progeny. Six groups of male and female mice were studied: wild type (WT) with wild receptors (WT/W), TG with wild receptors (TG/W), TG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 33 publications
7
111
0
2
Order By: Relevance
“…TNF-␣ is a 17-kDa polypeptide that specifically binds and exerts its function via two cell surface receptors, TNFR1 (p55) and TNFR2 (p75). Each TNF receptor has been shown to activate distinct signaling pathways with a small degree of overlap (26,27). Functions of TNFR1/p55 have been well studied and described (28,29).…”
Section: Radiation-induced Bystander Responses (Rbr)mentioning
confidence: 99%
See 1 more Smart Citation
“…TNF-␣ is a 17-kDa polypeptide that specifically binds and exerts its function via two cell surface receptors, TNFR1 (p55) and TNFR2 (p75). Each TNF receptor has been shown to activate distinct signaling pathways with a small degree of overlap (26,27). Functions of TNFR1/p55 have been well studied and described (28,29).…”
Section: Radiation-induced Bystander Responses (Rbr)mentioning
confidence: 99%
“…In contrast, TNFR2/p75 is generally pro-survival and pro-angiogenic and responsible for cell protective effects of TNF but regulates inflammatory signaling as well (30,31,(33)(34)(35). Both TNF receptors are ubiquitously expressed on nearly all cell types, but the p75 receptor is predominantly expressed by lymphoid cells as well as other hematopoietic and endothelial lineage cells, including endothelial progenitor cells (EPCs) (27,36,37). TNF induces inflammation via activation of transcription factor NF-B and its downstream targets: COX-2, MMP1, IL-1␣, IL-1␤, IL-6, IL-8, IL-33, insulin growth factor 1 (IGF-1), and TNF itself, along with many other cytokines (9).…”
Section: Radiation-induced Bystander Responses (Rbr)mentioning
confidence: 99%
“…Transgenic animal studies have shown that reduced Tnfrsf1b mRNA expression is associated with endothelial apoptosis [27] and increased risk of heart failure [28], while increased Tnfrsf1b mRNA expression is associated with ischemia-mediated adaptive angiogenesis [29]. Further, increased TNFRSF1B protein expression is associated with tubular cell regeneration in kidney tissue [30].…”
Section: Ckd) Is Timelymentioning
confidence: 99%
“…We suspected that some of the inflammatory effects of NF-κB could be mediated by its target gene TNF-α, which by itself can induce cardiomyopathy (20). However, the phenotype could not be rescued by ablation of TNFR1, the receptor considered the mediator of the deleterious effects of TNF-α (21). Vice versa, NF-κB may still mediate some of the detrimental effects of TNF-α (22, 23) Importantly, KO of TNFR1 improves heart function after coronary artery ligation, which correlates with decreased NF-κB activation (22).…”
Section: Role Of Chemokines Cytokines Adhesion Molecules and Myd88mentioning
confidence: 99%